El urbanismo francés en Venezuela de 1936 a 1950 (Rotival y Lambert en una historia de gestiones diplomáticas, contratos y zancadillas) - Martín Frechilla, Juan José (El Colegio de México A.C., 1993)
This study makes use of documentary sources from the archives of the French diplomatic corp and Venezuelan municipal agencies to reconstruct the process by which French urban development ideas were introduced and disseminated in Venezuela from 1936 through the decade of the 1950's. The story is traced through the activities of urban planners Maurice Rotival and Jacques Lambert and the role they played in the institutional organization of urban planning in Venezuela.Their influence, which took hold at the municipal level beginning with the creation of the Department of Urban Development and the Caracas Global Plan completed in 1939, would be consolidated after World War II - in spite of Rotival's increasingly favorable disposition toward currents developing in the United States - with the creation of the National Urbanism Commission as the first national planning agency.The impact of the two planners was also felt through their development of human resources.